2015
DOI: 10.1007/s11745-015-3993-0
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoinositide 3‐Kinase Signaling Pathway is Involved in the Control of Modified Low‐Density Lipoprotein Uptake by Human Macrophages

Abstract: The transformation of macrophages into lipid-loaded foam cells is a critical early event in the pathogenesis of atherosclerosis. Both receptor-mediated uptake of modified LDL, mediated primarily by scavenger receptors-A (SR-A) and CD36 along with other proteins such as lipoprotein lipase (LPL), and macropinocytosis contribute to macrophage foam cell formation. The signaling pathways that are involved in the control of foam cell formation are not fully understood. In this study, we have investigated the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Although we found that PI3K participates in the phagocytosis of S. typhimurium, we wanted to determine how PI3K influences the phagocytosis of S. typhimurium. Several studies have shown that inhibition of PI3K reduces the expression of scavenger receptors [29] and suppresses the adhesion of monocytes/macrophages [30]. Our data show that inhibition of PI3K by LY294002 not only reduced the expression of scavenger receptors, but also suppressed the adhesion of the cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although we found that PI3K participates in the phagocytosis of S. typhimurium, we wanted to determine how PI3K influences the phagocytosis of S. typhimurium. Several studies have shown that inhibition of PI3K reduces the expression of scavenger receptors [29] and suppresses the adhesion of monocytes/macrophages [30]. Our data show that inhibition of PI3K by LY294002 not only reduced the expression of scavenger receptors, but also suppressed the adhesion of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, CD36 has been implicated in actin cytoskeleton rearrangement [28]. Inhibition of PI3K can decrease the expression of scavenger receptors [29] and influence scavenger receptor-mediated cell adhesion [30]. These results suggest the possible interactions among TLR4, scavenger receptors, and PI3K during bacterial internalization.…”
Section: Introductionmentioning
confidence: 96%
“…These findings showed that Rab5 played an important role in the maturation of foam cells. Previous study demonstrated the critical role of PI3K signaling played in the uptake of modified LDL via its up-regulation effect on SRs, which in turn affects the maturation of foam cells [ 21 ]. Based on the analysis mentioned as above, the formation of foam cells may be driven by the association of Rab5 with PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…transcytosis-related proteins; and attenuate atherosclerosis (Gareus et al 2008;Zhang et al 2014). The suppression of PI3K is also reported to attenuate the uptake of LDL (Michael et al 2015). Through the regulation of NF-B and PI3K-AKT signaling pathways, shikonin inhibits the growth (Shi and Cao 2014;Wang et al 2014b;Tian et al 2015), invasion, and metastasis (Min et al 2011;Chen et al 2014) of cells, although most studies are performed in tumor cells.…”
Section: Discussionmentioning
confidence: 99%